Role of Sub-Conjunctival Bevacizumab in Regression of Corneal Neovascularization - Akhunzada Muhammad Aftab, Ibrar Hussain (Pakistan Journal of Ophthalmology, 2018)
Purpose: To evaluate therapeutic effect of subconjunctival bevacizumab on corneal neovascularization. Material and Methods: Thirty two eyes, with corneal neovascularization caused by different ocular surface disorders, were studied. Each eye received 2 injections of 2.5 mg/0.1ml bevacizumab at monthly interval. Morphological changes in corneal neovessels were evaluated using slit lamp biomicroscopy and digital corneal photography. Results: Out of total 32 patients, 21(65.5%) were males and 11(35.5%) were females. Mean age of all patients was 41.59 ± 17.6 years. Causes of corneal neovascularization included trauma (28.1%), failed corneal graft (21.9%), chemical burn (12.5%), healed corneal ulcer (12.5%), trachoma (3.1%) and unknown cause (21.9%). Mean corneal surface involved by neovessels before injection was 50.56 ± 30.4% which reduced to 35.81 ± 26.94% after sub-conjunctival injection of bevacizumab (p = 0.000) and the extent of neovessels reduced from 7.47 ± 3.83 clock hours to 6.56 ± 3.78 clock hours (p = 0.002). No adverse effect of subconjunctival bevacizumab was noted. Conclusion: Sub-conjunctival bevacizumab is effective in regressing corneal neovessels partially due to different causes. But for this purpose repeated injections are needed.